ASSESSING FLEXIBILITY IN REAL ESTATE MASS HOUSING - Gilani, Golshid; Turker, Ozlem Olgac (Editora Unisinos, 2020)
One of the most important considerations in housing design is flexibility, which refers to the idea of including change overtime. In looking at recent residential architecture of Cyprus, especially in real estate housing as a subset of mass housing, unfortunately, flexibility is not considered enough as a leading concept. The aim of this research is to evaluate notions and stages of flexibility in real estate housing projects in a recently developed residential context on the Salamis coastal line between the cities of Famagusta and Trikomo. The first step is flexibility assessment from an architectural perspective, through analyzing the architectural drawings of the projects to find out the potential for long term flexibility in terms of 'structural', 'functional' and 'cultural' notions; whereas, the second step is evaluating flexibility in three phases as 'design', 'construction' and 'usage' stages through questionnaire surveys with both construction companies and users. The results indicate the flexibility from the company's perspective and defragment the inhabitants' external and interior flexibility needs in three different stages, highlighting the role of companies and architects in designing flexible housing that can adapt to various users and their changing needs and preferences.
Keywords: Adaptability; user needs; flexibility stages; interior space; architecture